Soil pH Effects on Nutrient Availability in the Everglades Agricultural Area - Alan L. Wright; Edward A. Hanlon; David Sui; Ronald W. Rice (EDIS)
SL287, a 5-page fact sheet by Alan L. Wright, Edward A. Hanlon, David Sui, and Ronald Rice, identifies strategies that could be used to address the problem of the increasing pH in muck soils. Includes additional sources of information. Published by the UF Department of Soil and Water Science, May 2009.